The Dark Side of Bot Farms in the Business World: An Ethical and Economic Threat in the Digital Era - Ari Fajar Santoso; Zafar Khan (Bincang Sains dan Teknologi, 2025)
In the digital economy, bot farms have emerged as a controversial tool businesses use to manipulate online visibility and influence consumer perception. While automation offers efficiency, bots' misuse, primarily through coordinated bot farms, poses serious ethical, legal, and economic challenges. This article critically examines the negative impact of bot farms in business practices, focusing on deceptive marketing, unfair competition, consumer misinformation, and the distortion of digital ecosystems. Using qualitative analysis and literature review, this study highlights the urgent need for regulatory frameworks and ethical digital governance to combat the rise of bot-driven manipulation. The findings show that bot farms undermine trust, disrupt market fairness, and erode the integrity of online platforms, calling for cross-sector efforts to mitigate their spread.